Muslim Minority in Myanmar: A Case Study of Myanmar Government and Rohingya Muslims - Ismail Suardi Wekke; Hasbi Hasbi; M Mawardin; Suyatno Ladiqi; Mohd Afandi Salleh (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2017)
The discrimination suffered by Rohingya Muslims is increasingly blewed up in media in last decade. The peak of the discriminatory treatment against Rohingya Muslim by Myanmar government is the unavailability of shelter from Myanmar government. In the perspective of international law, Myanmar government's actions constitute a serious violence, because it ignores the rights of its citizens. Even a series of massacres and inhumane treatment became a major offense committed by Myanmar government in terms of humanity. This attracted international attention in solving the problem. This article illustrated the fate of Rohingyas who are not given citizenship rights by Myanmar government. It also revealed the irony of Muslims of Rohingya life who are discriminated by the government of Myanmar, both in the practical as well as in the political context.